Modelling the Logistics Response to a General Infectious Disease. Issue 3 (2015) - Chen, W.; Gurnet, A.; Ruiz, A.
Abstract: As an infectious disease has serious consequences and demands medical resources suddenly, an emergency management plan which can reduce the number of deaths should be studied. However, the papers in this area are still few and no paper proposes a model which can be adapted to general infectious diseases. This paper proposes a model which links the disease progression, the related medical intervention actions and the logistics deployment altogether to support the decision making process in case of the logistics response to an infectious disease from a strategic level. The number of the patients in different disease stages and the required medical resources for each period can be estimated by our model. The factors which have a great impact on the number of deaths can also be evaluated by this model. Numerical results take the H5N1 as an example to assess the potential contribution of our model.